Does a Screening Trial for Spinal Cord Stimulation in Patients With Chronic Pain of Neuropathic Origin Have Clinical Utility (TRIAL-STIM)? 36-Month Results From a Randomized Controlled Trial. Issue 1 (13th January 2023) - Eldabe, Sam; Nevitt, Sarah; Griffiths, Sara; Gulve, Ashish; Thomson, Simon; Baranidharan, Ganesan; Houten, Rachel; Brookes, Morag; Kansal, Anu; Earle, Jenny; Bell, Jill; Taylor, Rod S.; et al.
Abstract : BACKGROUND: Screening trials before full implantation of a spinal cord stimulation device are recommended by clinical guidelines and regulators, although there is limited evidence for their use. The TRIAL-STIM study showed that a screening trial strategy does not provide superior patient pain outcome at 6-month follow-up compared with not doing a screening trial and that it was not cost-effective. OBJECTIVE: To report the long-term follow-up results of the TRIAL-STIM study. METHODS: The primary outcome of this pragmatic randomized controlled trial was pain intensity as measured on a numerical rating scale (NRS) and secondary outcomes were the proportion of patients achieving at least 50% and 30% pain relief at 6 months, health-related quality of life, and complication rates. RESULTS: Thirty patients allocated to the "Trial Group" (TG) and 36 patients allocated to the "No Trial Group" (NTG) completed outcome assessment at 36-month follow-up. Although there was a reduction in NRS pain and improvements in utility scores from baseline to 36 months in both groups, there was no difference in the primary outcome of pain intensity NRS between TG and NTG (adjusted mean difference: −0.60, 95% CI: −1.83 to 0.63), EuroQol-5 Dimension utility values (adjusted mean difference: −0.02, 95% CI: −0.13 to 0.10), or proportion of pain responders (33% TG vs 31% NTG). No differences were observed between the groups for the likelihood of spinal cord stimulation device explant or reporting an adverse advent up to 36-month follow-up. CONCLUSION: The long-term results show no patient outcome benefit in undertaking an SCS screening trial.